2013
DOI: 10.1186/1471-2474-14-196
|View full text |Cite
|
Sign up to set email alerts
|

Detecting insomnia in patients with low back pain: accuracy of four self-report sleep measures

Abstract: BackgroundAlthough insomnia is common in patients with low back pain (LBP), it is unknown whether commonly used self-report sleep measures are sufficiently accurate to screen for insomnia in the LBP population. This study investigated the discriminatory properties of the Pittsburgh Sleep Quality Index (Pittsburgh questionnaire), Insomnia Severity Index (Insomnia index), Epworth Sleepiness Scale (Epworth scale) and the sleep item of the Roland and Morris Disability Questionnaire (Roland item) to detect insomnia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 38 publications
7
39
0
2
Order By: Relevance
“…Alsaadi and his colleagues found similar results and showed that back pain and sleep disorders were associated with each other (Alsaadi et al, 2013). Sleep disorders can exacerbate pain and inflammatory processes.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Alsaadi and his colleagues found similar results and showed that back pain and sleep disorders were associated with each other (Alsaadi et al, 2013). Sleep disorders can exacerbate pain and inflammatory processes.…”
Section: Discussionsupporting
confidence: 65%
“…Scores higher is related to the quality of sleep are more unfavorable (Buysse, Reynolds, Monk, Berman, & Kupfer, 1989). Reliability and validity of this questionnaire have been confirmed in other studies (Alsaadi et al, 2013;Farhadi Nasab & Azimi, 2008;Mollayeva et al, 2015). According to the designers of the questionnaire, a score greater than 5 indicates a poor sleep quality (Ağargün, Kara, & Anlar, 1996;Aloba, Adewuya, Ola, & Mapayi, 2007;Doi et al, 2000).…”
Section: Sleep Quality Assessmentsupporting
confidence: 49%
“…Any score higher than 5 is regarded as poor sleep quality. The validity of the questionnaire has been confirmed in the earlier studies (Alsaadi et al, 2013;Nasab, & Azimi 2008).…”
Section: Methodssupporting
confidence: 62%
“…The higher score demonstrates the higher risk of insomnia and need for medical assistance. The questionnaire was used by Morine and his coworkers for the first time (Alsaadi et al, 2013). The Kronbach' alpha of the questionnaire was 0.76 in the current study which is acceptable.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation